Knowledge and consumption of folic acid among teachers in Jammu region: a cross-sectional study - Choudhary, Neha; Manhas, Preeti; Narangyal, Akash; Manhas, Rohan Singh (International Journal Of Community Medicine And Public Health, 2021)
Background: Folic acid reduces the risk of birth defects, including neural tube defects (NTDs). It reduces the risk of miscarriage and fetal death as well as folate-deficiency anemia. Folate status is particularly important before conception and during the first 12 weeks of pregnancy. Objective was to assess knowledge and consumption of folic acid among teachers in the reproductive age group. Methods: 336 school teachers selected from government and private schools (primary/middle/secondary/higher secondary) by simple random sampling technique. Teacher’s knowledge and consumption of folic acid and associated factors was studied using a pre- tested; self- administered questionnaire. Results: 95% teachers had heard about folic acid, 57% knew about neural tube defects. 53% were aware of the role of folic acid in NTDs. 66% had knowledge about the best timing for its intake. 56% were aware about the sources rich in folic acid. 75% believed that foods are the best source of folic acid, 80% believed that taking foods rich in folic acid and tablets are sufficient to maintain body stores.49% were taking folic acid presently. 66% of the participants were taking folic acid under medical advice, 29% due to the recommendations by their family/friends while self-initiation was reported in only 5% of the individuals. Conclusions: IEC activities needs to be conducted among different strata of population so that the intake of folic acid could be increased and associated factors effecting its intake and absorption could be taken care of.